Endolysosomal transient receptor potential mucolipins and two-pore channels: implications for cancer immunity - Ouologuem, Lina; Bartel, Karin (Frontiers in Immunology, 2024)
Past research has identified that cancer cells sustain several cancer hallmarks by impairing function of the endolysosomal system (ES). Thus, maintaining the functional integrity of endolysosomes is crucial, which heavily relies on two key protein families: soluble hydrolases and endolysosomal membrane proteins. Particularly members of the TPC (two-pore channel) and TRPML (transient receptor potential mucolipins) families have emerged as essential regulators of ES function as a potential target in cancer therapy. Targeting TPCs and TRPMLs has demonstrated significant impact on multiple cancer hallmarks, including proliferation, growth, migration, and angiogenesis both in vitro and in vivo.Notably, endosomes and lysosomes also actively participate in various immune regulatory mechanisms, such as phagocytosis, antigen presentation, and the release of proinflammatory mediators.Yet, knowledge about the role of TPCs and TRPMLs in immunity is scarce. This prompts a discussion regarding the potential role of endolysosomal ion channels in aiding cancers to evade immune surveillance and destruction. Specifically, understanding the interplay between endolysosomal ion channels and cancer immunity becomes crucial. Our review aims to comprehensively explore the current knowledge surrounding the roles of TPCs and TRPMLs in immunity, whilst emphasizing the critical need to elucidate their specific contributions to cancer immunity by pointing out current research gaps that should be addressed.